2018
DOI: 10.1111/jep.12932
|View full text |Cite
|
Sign up to set email alerts
|

What difference do brain images make in US criminal trials?

Abstract: One of the early concerns regarding the use of neuroscience data in criminal trials is that even if the brain images are ambiguous or inconclusive, they still might influence a jury in virtue of the fact that they appear easy to understand. By appearing visually simple, even though they are really statistically constructed maps with a host of assumptions built into them, a lay jury or a judge might take brain scans to be more reliable or relevant than they actually are. Should courts exclude brain scans for be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For instance, Berryessa [16] found that potential jurors given evidence of biological risk factors rated the defendant as less responsible for their acts and more likely to commit future crimes compared to those not given biological risk factor information. This potential of biological evidence to cut both ways in a defendant’s case has been described as a double-edged sword [7, 1719]. If admission of such evidence carries this risk, it has important implications for how legal parties present evidence, how judges and jurors evaluate that evidence, and more broadly how human beings make moral judgments.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Berryessa [16] found that potential jurors given evidence of biological risk factors rated the defendant as less responsible for their acts and more likely to commit future crimes compared to those not given biological risk factor information. This potential of biological evidence to cut both ways in a defendant’s case has been described as a double-edged sword [7, 1719]. If admission of such evidence carries this risk, it has important implications for how legal parties present evidence, how judges and jurors evaluate that evidence, and more broadly how human beings make moral judgments.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is more consistent with mitigation than insanity. 39 A final consideration of concerns about objectivity center around the innovation that remains with neuroimaging and the iterative nature of science regarding this technology. No finding highlights problematic correlations that can arise in scanning without objective interpretation more than when functional activity was found during scans performed on a deceased salmon that clearly had no functional activity.…”
Section: Neuroimaging and Responsibility: Application To Retrospective Evaluation Of Mental Statementioning
confidence: 99%
“…How do we perform the imperative of the normative responsibility (and Law is normative by definition) when providing statements grounded on entirely subjective evaluation (interviews and/or self‐assessments)? In answer to these questions, Hardcastle and Lamb's contribution to the Special Section provides many valuable insights . Finally, the last Century has witnessed the adoption of an outdated dichotomy, as defined in the neo‐Kantian tradition, and attributed to the German philosopher Wilhelm Windelband .…”
Section: Translating the Findings Of Neuroscience Into Clinical Medicmentioning
confidence: 99%